CONTRAST CRITERIA OF SYMMETRIC SYSTEMS OF WALSH FUNCTIONS - Біленький, А. Я.; Кучер, О. Г. (Proceedings of National Aviation University (archive), 2021)
Quantitative estimates characterizing the degree of divergence of symmetric systems of Walsh functions are considered.